2013
DOI: 10.1002/pc.22759
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillated cellulose, poly(vinyl alcohol), montmorillonite clay hybrid nanocomposites with superior barrier and thermomechanical properties

Abstract: Nanocomposites of poly(vinyl alcohol) (PVA), nanofibrillated cellulose (NFC), and montmorillonite (MMT) clay were prepared via solvent casting. In addition to investigating the effect of clay loading, PVA matrices crosslinked with poly(acrylic acid) (PAA) were prepared and compared with linear (noncrosslinked) PVA nanocomposites. 13C NMR and infrared spectroscopy confirmed the presence of crosslinks. Scanning electron microscopy revealed effective NFC and MMT clay dispersion throughout the nanocomposites, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 81 publications
1
51
0
Order By: Relevance
“…Nanopapers (Ferrer et al, 2011a,b) or nanocellulose films have been reported for their unique properties such as low density, low porosity, transparency, low coefficient of thermal expansion, low air permeability and high strength (Moon et al 2011). The porosity of nanopapers prepared using CNF is typically very low, this enables their good gas barrier properties (Syverud and Stenius 2009;Tammelin and Vartiainen 2014). However, depending on the intended application porous materials may be preferred, for example in membranes carrying exposed adsorption sites for target molecules as is the case of systems enclosing cellulose nanocrystals that have been developed for dye removal from water (Karim et al 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Nanopapers (Ferrer et al, 2011a,b) or nanocellulose films have been reported for their unique properties such as low density, low porosity, transparency, low coefficient of thermal expansion, low air permeability and high strength (Moon et al 2011). The porosity of nanopapers prepared using CNF is typically very low, this enables their good gas barrier properties (Syverud and Stenius 2009;Tammelin and Vartiainen 2014). However, depending on the intended application porous materials may be preferred, for example in membranes carrying exposed adsorption sites for target molecules as is the case of systems enclosing cellulose nanocrystals that have been developed for dye removal from water (Karim et al 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…5,40 The incorporation of clay platelets into polymers initially attracted attention because of improvements in mechanical properties of polymer. 33,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69] The most widely used clay ller for the enhancement of gas barrier property of PNCs is MMT as it has large cation exchange capacity. 33,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69] The most widely used clay ller for the enhancement of gas barrier property of PNCs is MMT as it has large cation exchange capacity.…”
Section: Exfoliation Of Layered Clay Into Individual Plateletsmentioning
confidence: 99%
“…44 Xie et al modied MMT with dodecyl dimethylbenzyl ammonium (DDA) and octadecyl trimethyl ammonium (OTA) salt. 33 Recently, LbL assembly has been applied as a simple and versatile thin-lm fabrication technique. The CO 2 and O 2 barrier properties of nanocomposites were found to increase by 7 times and 4 times with 0.5 wt% O-MMT loading, respectively.…”
Section: Gas Barrier Properties Of Polymer/ Clay Nanocompositesmentioning
confidence: 99%
“…Owing to the intriguing properties of CNFs, a variety of high-end applications have been proposed. The optical transparency and excellent mechanical properties of CNFs make them suitable in coating and packaging applications (Lavoine et al 2014;Spoljaric et al 2014;Azeredo et al 2015;Kumar et al 2016). Flexible screens (Okahisa et al 2009), supercapacitors and batteries (Hamedi et al 2013;Nyström et al 2015) are also among the applications for which nanocelluloses have been suggested.…”
Section: Introductionmentioning
confidence: 99%